1969
DOI: 10.1901/jaba.1969.2-49
|View full text |Cite
|
Sign up to set email alerts
|

Academic Response Rate as a Function of Teacher‐ and Self‐imposed Contingencies

Abstract: The purpose of this study was to assess the effects of the contingency manager (teacher or pupil) on a pupil's academic response rate. The results of two such experiments disclosed that higher academic rates occurred when the pupil arranged the contingency requirements than when the teacher specified them. A third study manipulated only reinforcement magnitude to ascertain whether amount of reinforcement had interacted with pupil-specified contingencies to produce the increase in academic response rate. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
2
2

Year Published

1972
1972
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(71 citation statements)
references
References 0 publications
4
63
2
2
Order By: Relevance
“…In general, the results of this and other investigations (Johnson, 1970;Johnson and Martin, 1972;Lovitt and Curtiss, 1969;Glynn, 1970) are clear. Self-regulation procedures appear to be either equally effective or more effective than external regulation procedures in both establishing and maintaining desired changes in behavior.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In general, the results of this and other investigations (Johnson, 1970;Johnson and Martin, 1972;Lovitt and Curtiss, 1969;Glynn, 1970) are clear. Self-regulation procedures appear to be either equally effective or more effective than external regulation procedures in both establishing and maintaining desired changes in behavior.…”
Section: Discussionsupporting
confidence: 78%
“…Lovitt and Curtiss (1969) demonstrated the potential of self-regulation for increasing a student's academic response rate. They found that higher academic rates occurred when the pupil arranged the contingency requirements than when the teacher specified them.…”
mentioning
confidence: 99%
“…Lovitt and Curtiss (1969) found that with a 12-yr-old student, higher rates of responding occurred when the student arranged the contingency requirements than when the teacher specified them. (SPRING 1973) ment magnitude, accounted for this subject's gain in performance.…”
mentioning
confidence: 99%
“…
Various studies have demonstrated the effectiveness of behavioral techniques in increasing in-class study behavior (Bushell, Wrobel, and Michaelis, 1968;Hall, Lund, and Jackson, 1968;Lovitt and Curtiss, 1969). In a college or university, however, the study behavior of concern is usually that which occurs outside the classroom, and usually requires the student to manage his own behavior.
…”
mentioning
confidence: 99%